Information technology training for Lebanese public school principals - Jabbour, Khayrazad Kari (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper focuses on an investigation into the role of information technology in the lives of Lebanese school principals. The objective of this research is to identify Lebanese school principals’ perceptions of the barriers, benefits and negative consequences of information technology usage by listening to their views and experiences. Findings of this research indicate that Lebanese school principals faced challenges including psychological and physical barriers to technology usage. This research can serve as a basis in making an informed decision about designing future information technology training sessions that can accommodate and serve the Lebanese school principals’ specific needs.